Physical activity among school-aged children and intervention programs using self-determination theory (SDT): A scoping review - Tameka STEWART; Manoj SHARMA (Journal of Health and Social Sciences)
Introduction: Moderate to vigorous physical activity (MVPA) among children is imperative for proper development. However, the problem of physical inactivity is a concern among many countries worldwide. Self-Determination Theory (SDT) has been widely used to develop interventions aimed at promoting auto- nomy for physical activity (PA) among children and adolescents. The aim of this scoping review was to eva- luate the efficacy of intervention studies based on SDT in promoting MVPA among school-aged children. Methods: PRISMA-ScR guidelines were used in conducting this scoping review. An electronic literature search in MEDLINE (PubMed), Google Scholar, ERIC, and Academic Search Premier was performed to identify intervention studies based on SDT aimed at promoting PA among school-aged children. Studies had to meet the following inclusion criteria: (i) participants were children or adolescents (between 5 and 18 years of age); (ii) a focus on promoting PA interventions; (iii) quantitative or mixed-method based, and (iv) intervention had to be based on SDT. Results: A total of 10 interventions met the eligibility criteria. Nine of the 10 studies were experimental studies and 1 observational, cross sectional study. A total of 2,577 children and adolescents participated in the 10 studies. Six studies utilized the randomized controlled trial design (RCT); only three studies de- monstrated a significant, consistent, increase of MVPA among the intervention groups; one of which was a RCT study. There was little to no increase in MVPA among girls within the research. Additionally, two studies revealed that children were more physically active as long as parents or teachers were involved. Discussion: The results of this scoping review showed insufficient evidence for the efficacy of intervention studies based on SDT in promoting MVPA among children and adolescents. Therefore, newer fourth-ge- neration theories such as the multi-theory-model (MTM) for health behavior change is suggested and can be tested by future interventions.